IMPLEMENTASI COLABORATIVE FOR ACADEMIC, SOSIAL AND EMOTIONAL LEARNING (CASEL) DALAM RUANG LINGKUP BUDAYA SEKOLAH DI SMP - Annisa Ika Wijayanti; Sumarno; Muhammad Saipul Hayat; Djoko Ichsanudin (STKIP Subang, 2023)
ABSTRACT Social emotional development is a very important aspect of development for every child because it is one of the determining factors for his or her success in the future. The CASEL framework provides indicators of social emotional learning in schools through integration in subjects and in school activities/school culture. This research describes the implementation of CASEL in school culture at SMP 36 Semarang. The core indicators of social emotional learning from the Collaborative for Academic Social and Emotional Learning (CASEL) are used to analyze social emotional development, namely self-awareness, self-management, social recognition (self-awareness), building skills relationships (relationship skills) and responsible decision making (responsible decision-making). A single instrumental case study type qualitative approach was chosen by the researcher to answer the research questions. The research results show that the five core indicators of social emotional learning are visible in the school culture of SMP 36 Semarang. ABSTRAK Perkembangan sosial emosional merupakan salah satu aspek perkembangan yang sangat penting bagi setiap anak karena merupakan salah satu faktor penentu kesuksesannya di masa depan. Kerangka CASEL memberikan indikator pembelajaran sosial emosional di sekolah melalui pengintegrasian dalam mata pelajaran maupun di kegiatan sekolah/budaya sekolah. Penelitian ini medeskripsikan tentang impelementasi CASEL dalam budaya sekolah di SMP 36 Semarang. Indikator inti pembelajaran sosial emosional dari Collaborative for Academic Social and Emotional Learning (CASEL) digunakan untuk menganalisis perkembangan sosial emosional, yaitu pengenalan diri (self-awareness), manajemen diri (self-management), pengenalan sosial (self-awareness), keterampilan membangun hubungan (relationship skill) dan pengambilan keputusan yang bertanggungjawab (responsible decition-making). Pendekatan kualitatif jenis studi kasus (case study) tunggal instrumental dipilih peneliti untuk menjawab pertanyaan penelitian. Hasil penelitian menunjukkan bahwa kelima indikator inti pembelajaran sosial emosional terlihat dalam budaya sekolah SMP 36 Semarang.